The Effect of Debate Technique towards Eleventh Grade Students’ Speaking Competency - Widiawati, Putu Shela; Ratminingsih, Ni Made; Agustini, Dewa Ayu Eka (Journal of Education Research and Evaluation, 2020)
Among the four pivotal skills, speaking signifies part of the most essential skill because its role primarily serves as a means of communication. Speaking is an interactive process of developing, creating, constructing and delivering meaning with goal of information exchanges between speaker and hearer. some students still faced some problems to communicate in English. Many students did not show their readiness in speaking English spontaneously.  This study aimed at investigating the significant effect of debate technique on students’ speaking competency, this quasi-experimental research employed 70 student participants from two social science classes, who were randomly assigned to the experimental condition and to the control condition. The instruments used for collecting the data were performance of speaking test and rubric for students’ speaking assessment. The data were analysed by using descriptive and inferential analyses. The result of this study shows that the mean score of experimental group is 79.79, while the mean score of control group is 75.25. The result of t test shows that the value of Sig. (2-tailed) is .000, which indicates a significant mean different. Therefore, this study concludes that debate technique affects students’ speaking competency. In addition to it, the contribution to the teaching of speaking as well as implications for future research are also discussed.